2023
DOI: 10.3390/inorganics11010032
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Thermal Investigations of Eutectic Metallomesogen Mixtures Based on Salicylaldiaminates Metal Complexes with a Large Nematic Stability Range

Abstract: The mesomorphic behavior and the miscibility properties of binary mixtures of a new series of Schiff base metallomesogen (MOM) are evaluated by differential scanning calorimetry (DSC) and polarized optical microscopy (POM). Nuclear magnetic resonance (NMR), elemental analysis (CHNX), Fourier−transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA) were used to certify the molecular structure of the compounds. The results revealed that the studied mixtures are completely miscible throughout t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…The details of synthetic procesdures, transitions temperatures and mesogenic phases of this class of bi-ligand MOM chemistry have been reported elsewhere. [33][34][35][36][37][38][39]40 The utilized commercial Nematic Liquid Crystal (NLC) materials in this study include TN10427, TNO623 (Hofmann La Roche) and E43 (Merck). All NLC materials were used as such and details of their transition temperatures have been mentioned elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…The details of synthetic procesdures, transitions temperatures and mesogenic phases of this class of bi-ligand MOM chemistry have been reported elsewhere. [33][34][35][36][37][38][39]40 The utilized commercial Nematic Liquid Crystal (NLC) materials in this study include TN10427, TNO623 (Hofmann La Roche) and E43 (Merck). All NLC materials were used as such and details of their transition temperatures have been mentioned elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, any hope for development of commercial MOM materials, will be possible not only through molecular engineering and synthesis, but also by complementary mixing approach as has been done for commercial liquid crystal products. In this respect, we are reporting the study of this approach on the miscibility of rodlike bi-ligand MOM complexes based on salicylal-diaminates structures and we provided the phase diagrams of their binary mixtures with different metals and ligands by physical mixing method (Hakemi & Roviello, 2022). The preliminary results indicated that these MOMs mixtures exhibited complete mesogenic miscibility, distinct eutectic points and wide mesogenic range.…”
Section: Introductionmentioning
confidence: 99%